2020
DOI: 10.3390/ijms21228681
|View full text |Cite
|
Sign up to set email alerts
|

Double Gamers—Can Modified Natural Regulators of Higher Plants Act as Antagonists against Phytopathogens? The Case of Jasmonic Acid Derivatives

Abstract: As key players in biotic stress response of plants, jasmonic acid (JA) and its derivatives cover a specific and prominent role in pathogens-mediated signaling and hence are promising candidates for a sustainable management of phytopathogenic fungi. Recently, JA directed antimicrobial effects on plant pathogens has been suggested, supporting the theory of oxylipins as double gamers in plant-pathogen interaction. Based on these premises, six derivatives (dihydrojasmone and cis-jasmone, two thiosemicarbazonic der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…A great variability of efficacy was observed amongst compounds: derivatives from benzaldehyde, benzophenone, cuminaldehyde, cinnamaldehyde, 2-acetylthiophene and cis -jasmone parent compounds proved to be the most active compounds ( Tables S1 and S2 ) [ 23 , 27 , 29 , 32 , 33 , 34 ], while many others did not show any interesting activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A great variability of efficacy was observed amongst compounds: derivatives from benzaldehyde, benzophenone, cuminaldehyde, cinnamaldehyde, 2-acetylthiophene and cis -jasmone parent compounds proved to be the most active compounds ( Tables S1 and S2 ) [ 23 , 27 , 29 , 32 , 33 , 34 ], while many others did not show any interesting activity.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, the pre-existing biological activity could be enhanced by specific structural modifications. Several researches have proposed natural compounds or their chemical analogues as crop-protective agents; additionally, metallic ions such as copper and zinc have been long time used for their fungicidal properties, demonstrating containment effects on the growth of phytopathogenic fungi and mycotoxins production [ 27 , 29 , 34 ]. In our study, we screened an extended panel of natural compounds and synthesized derivatives in order to individuate—and possibly ameliorate—effective antifungal and/or anti-aflatoxigenic molecules against A. flavus , being reasonably safe for the health of the stakeholders and the environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LC-based lipidomics is relatively rapid and usually requires less sample than GC-derived methods, since only 2–10 mg of leaf dry weight is needed, but these advanced techniques only recently have been applied on bryophytes extracts: in 2017, Gacet and coauthors employed targeted metabolomics using LC–MS/MS and GC–MS to study signaling lipids in 71 plant species, representative of major phylogenetic clades, to systematically investigate the distribution of lipids in the plant kingdom; they found a fascinating positive phylogenetic correlation in the jasmonic acid (JA) abundance of early plants versus Angiosperms and Gymnosperms [ 194 ]. JA and its derivatives, jasmonates, belong to the class of oxylipins, bioactive metabolites derived from the oxygenation of acidic polyunsaturated fats [ 195 ]: besides primarily exerting regulatory functions involved in plant reproductive development and vegetative growth, jasmonates not only play critical roles in the defense response against wounds and attacks by pathogens, but also have been recently reported to possess a direct antifungal activity against a number of fungal phytopathogens [ 196 ]. Gachet et al demonstrated that, while completely absent in algae, JA started to be detected in small to intermediate amounts in bryophytes (namely: hornworts Anthoceros agrestis, Anthoceros punctatus and Phaeoceros laevis ; mosses Physcomitrella patens, Funaria hygrometrica, Polytrichum juniperinum, Hedwigia ciliata and Hylocomium splendens and liverworts Conocephalum conicum, Marchantia polymorpha and Riccia fluitans ), with the ending to be more represented in higher plants.…”
Section: Mining With the Omic-technologies: New Generation Approacmentioning
confidence: 99%